The Calculation of Photon Interactions in Gd2YAl2Ga3O12 compound by the Phy-X Software Compared with WinXCom Program - Cheewasukhanont, Wasu; Limkitjaroenporn, ‪Pruittipol; Kaewkhao, Jakrapong; Kaewnuam*, Eakgapon (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2022)
The photon interactions in Gd2YAl2Ga3O12 compound were studied in this work. The interaction parameters, such as total mass attenuation coefficient (μm), effective atomic number (Zeff), effective electron density (Neff), mean free path (MFP), half-value layer (HVL) and tenth-value layer (TVL) were computed as a function of energy between 1 keV-100 GeV, while the atomic equivalent (Zeq) and the buildup factors were calculated with 0.015 MeV-15 MeV energy range using Phy-X software. Moreover, all obtained values were compared with calculated ones using WinXCom program over the same energy range. Both calculation processes represent the μm reduction by following the energy increment. The Zeff and Neff show a similar trend depending on the energy range and have some discrete values at low energy. These discontinuous values correspond to the absorption edges which were also found in the μm calculation at same energy. The trends of MFP, HVL, and TVL are similar in that their highest values appear in the middle energy range with main interaction being Compton scattering. The buildup factors represent the multiple scattering of photons in materials and air with the main peaks in middle energy range. Keywords: radiation interaction; WinXCom program; Phy-X software *Corresponding author: (+66) 822156439 E-mail: eakgapon_9@hotmail.com